Enhancing elementary school student’s problem-solving abilities with interactive math multimedia - Noor Fazariah Handayani; Yenny Anggreini Sarumaha; Oesman Raliby; Septiana Ningtyas; Shofwatal Qolbiyyah (Sean Institute, 2024)
Utilizing interactive multimedia in learning, particularly mathematics in elementary schools, can aid students in comprehending concepts and enhancing their problem-solving abilities in the digital age. By utilizing interactive learning media, it is possible to surmount the obstacles of limited comprehension of the material and absence of enthusiasm for learning. By providing visual representations of the material, this media not only enhances students' comprehension of concepts but also motivates them to improve their mathematical abilities. This research employs interactive math multimedia in conjunction with the ADDIE model to enhance the problem-solving abilities of elementary school students. The findings indicated that digital learning materials designed for mathematics instruction possess an aesthetically pleasing visual presentation, encompassing both the animation of simple multiplication and division tasks and the portrayal of coloring. In addition to aiding in problem-solving, digital learning media for mathematics instruction can increase students' comprehension and interest in the subject matter, particularly when it comes to uncomplicated multiplication and division